2015
DOI: 10.3382/ps/pev237
|View full text |Cite
|
Sign up to set email alerts
|

Influence of feeding alternative fiber sources on the gastrointestinal fermentation, digestive enzyme activities and mucosa morphology of growing Greylag geese

Abstract: The objective of this trial was to study the influence of dietary fiber sources on the gastrointestinal fermentation, digestive enzyme activity, and mucosa morphology of growing Greylag geese. In total, 240 Greylag geese (28-day-old) were allocated to 4 treatments (15 pens/treatment) differing in dietary fiber source: corn straw silage (CSS group), steam-exploded corn straw (SECS group), steam-exploded wheat straw (SEWS group), or steam-exploded rice straw (SERS group). At 112 days of age, 15 birds per group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
0
16
0
3
Order By: Relevance
“…Each compartment of GIT and internal organs were removed from the abdominal cavity, stripping all attachments, large blood vessels, lymph nodes and fat tissue. Two 2-cm sections were removed from the duodenum (within 10 cm of pylorus), jejunum (estimated midpoint of small intestine), and ileum (within 10 cm of cecum) were collected and fixed in 10% formalin solution in preparation for morphometric analysis of villus lengths and crypt depths immediately, according to He et al (2015) [16]. The villus:crypt ratio was calculated as the villus length divided by crypt depth.…”
Section: Methodsmentioning
confidence: 99%
“…Each compartment of GIT and internal organs were removed from the abdominal cavity, stripping all attachments, large blood vessels, lymph nodes and fat tissue. Two 2-cm sections were removed from the duodenum (within 10 cm of pylorus), jejunum (estimated midpoint of small intestine), and ileum (within 10 cm of cecum) were collected and fixed in 10% formalin solution in preparation for morphometric analysis of villus lengths and crypt depths immediately, according to He et al (2015) [16]. The villus:crypt ratio was calculated as the villus length divided by crypt depth.…”
Section: Methodsmentioning
confidence: 99%
“…Coarse feed particles remain longer in the upper part of the GIT, stimulating gizzard activity (Hetland et al 2005) and increasing the production of HCl (Duke 1986). A low gizzard pH improves pepsin activity and nitrogen retention and increases the solubility of the mineral fraction of the feed (Guinotte et al 1995), which in turn can favour its absorption. Souffrant (2001) and Hetland et al (2005) reported that, because of its nonviscous nature, insoluble NSP may have beneficial effects on digestive processes.…”
Section: Performancementioning
confidence: 99%
“…One possible alternative control of enteric disease is by changing feed composition and uses various dietary interventions (Armstrong 2016). Many studies have been performed to change gut health and microbial populations by adding types of fibrous fractions into poultry diets (He et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One alternative that may very well have a positive effect on feed intake ( FI ), growth and development, gut structure and digestibility, and the overall health in poultry is fiber ( Mateos et al., 2012 , He et al., 2015 , Jiménez–Moreno et al., 2016 , Kheravii et al., 2017 ). It is already known that the potential effects of dietary fiber are related to the physicochemical characteristics and structure of the fiber source ( Raninen et al., 2011 , Yokhana et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%